2005
DOI: 10.1111/j.1439-037x.2004.00133.x
|View full text |Cite
|
Sign up to set email alerts
|

Winter Wheat Cultivar Responses to Fungicide Application are Affected by Nitrogen Fertilization Rate

Abstract: Foliar fungicides are important management inputs for winter wheat (Triticum aestivum L.) in high-yielding areas of Europe, but their effectiveness may interact with cultivar selection and nitrogen (N) fertilization. No information is available on the potential use of fungicides in reducing yield losses from foliar diseases in Croatia, where wheat crop is extensively grown under low N inputs. Field experiments were conducted during 2000-02 to evaluate the agronomic responses of six winter wheat cultivars to fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0
14

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 19 publications
4
14
0
14
Order By: Relevance
“…Some studies have demonstrated a significant influence of N fertilizer on powdery mildew, with a strong positive correlation between N rate and severity index of the disease and a significant negative correlation between grain yield and disease index (Zhang and Zhang 1991;Gao et al 1993). Wheat grain yield and product quality were found to be substantially influenced by N nutrition (Guttieri et al 2005;Varga et al 2005) and foliar disease (Puppala et al 1998), and N utilization and management are recognized as very important factors in wheat production (Olesen et al 2000;Kratochvil et al 2005). Numerous studies have indicated the advantageous effects of various cultural practices on disease control and higher yields, including mixtures of several varieties (Mundt 2002;Cox et al 2004) or intercropping wheat with other species (Trenbath 1993;Zhu et al 2004) and N fertilizer utilization associated with fungicide application (Varga et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated a significant influence of N fertilizer on powdery mildew, with a strong positive correlation between N rate and severity index of the disease and a significant negative correlation between grain yield and disease index (Zhang and Zhang 1991;Gao et al 1993). Wheat grain yield and product quality were found to be substantially influenced by N nutrition (Guttieri et al 2005;Varga et al 2005) and foliar disease (Puppala et al 1998), and N utilization and management are recognized as very important factors in wheat production (Olesen et al 2000;Kratochvil et al 2005). Numerous studies have indicated the advantageous effects of various cultural practices on disease control and higher yields, including mixtures of several varieties (Mundt 2002;Cox et al 2004) or intercropping wheat with other species (Trenbath 1993;Zhu et al 2004) and N fertilizer utilization associated with fungicide application (Varga et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In this research, five different fungicides were used as chemical treatment on wheat leaves at appearance of fungal disease symptoms. Spray of fungicides reduced fungal infections especially and improved wheat yields (Varga et al, 2005;Carmona et al, 1999).…”
Section: Management Strategiesmentioning
confidence: 99%
“…Increased yields disease management are associated mainly with an increase in thousand grain weight [72,73,78,79,80], while other yield components such as number of spikes.m -2 [72] or grains.spike -1 [72,79,80,81] are usually not affected by disease severity. However, Simón et al [82] reported that preventing early wheat infection by Septoria tritici could result in an increase of spikes.m -2 and grains.spike -1 .…”
Section: The Use Of Fungicides In the Integrated Foliar Disease Managmentioning
confidence: 99%
“…Management practices such as N fertilization can also affect the expression of wheat foliar diseases [82,84] and the effectiveness of foliar fungicide application [72,82,84,85]. Increasing N rates may cause negative, positive or neutral effect on foliar disease severity, depending on the geographic location [86] and the type of disease.…”
Section: The Use Of Fungicides In the Integrated Foliar Disease Managmentioning
confidence: 99%
See 1 more Smart Citation